Methods for treating lyocell fibres

JP7661224B2Active Publication Date: 2025-04-14LENZING AG
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
JP2021532383
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-12-17
Filing Date
2019-12-13
Publication Date
2025-04-14
Estimated Expiration
2039-12-13

AI Technical Summary

Technical Problem

Existing methods for treating lyocell fibers to prevent fibrillation are unable to provide stable and permanent protection against fibrillation under both acidic and alkaline conditions, which is essential for textile processing and washing.

Method used

A method of treating lyocell fibers by contacting them with a crosslinker that is capable of crosslinking cellulose under alkaline conditions, and applying the crosslinker in the form of a suspension or solid, rather than a solution, to ensure stable and permanent fibrillation protection.

Benefits of technology

The method achieves stable and permanent fibrillation protection, as evidenced by high wet wear values and minimal change in Canadian Standard Filtration values, even after blending for extended periods, and withstands various textile processing conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007661224000002
    Figure 0007661224000002
  • Figure 0007661224000003
    Figure 0007661224000003
  • Figure 0007661224000001
    Figure 0007661224000001
Patent Text Reader

Abstract

The present invention relates to a method for treating lyocell fibers, comprising the steps of contacting the fibers with at least one treatment medium, the at least one treatment medium containing an amount of a crosslinking agent capable of crosslinking cellulose under alkaline conditions and having a solubility in water at 20°C of not more than 20 g / l, and treating the fibers with the crosslinking agent under alkaline conditions, characterized in that the crosslinking agent is added to the fibers in the form of a suspension or in solid form. The present invention also relates to lyocell fibers obtainable by the method of the present invention.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for treating lyocell fibers and to the lyocell fibers obtainable by the method of the present invention. [Background technology]

[0002] The term "lyocell" is the generic name assigned by BISFA (International Bureau of Standardization of Man-Made Fibers) to cellulose fibers produced by dissolving cellulose in an organic solvent without forming derivatives and extruding fibers from said solution by a dry-wet spinning process or by a meltblown process. Currently, on a commercial scale, N-methyl-morpholine-N-oxide (NMMO) is used as the organic solvent.

[0003] In the process, a solution of cellulose is typically extruded through a forming tool and thereby shaped. The shaped solution passes through an air gap into a precipitation tank where the shaped bodies are obtained by precipitating the solution. The shaped bodies are washed and, after further processing steps, dried if necessary. The amine oxide solvent is recycled in a closed loop in the plant. Recovery rates of more than 99.5% have been achieved. Recycling of the additives means that the impact of the process on the environment is very low. This is also essential for the economics of the process.

[0004] Methods for producing standard lyocell fibers are known, inter alia, from U.S. Pat. No. 4,246,221 or WO 93 / 19230. Lyocell fibers are characterized by high tensile strength, high wet modulus and high loop strength. They are used in apparel, home furnishings, workwear and nonwoven articles. Commercially available fibers are, for example, manufactured by Lenzing AG and are trademarked as TENCEL® Lyocell.

[0005] It is well known that Lyocell fibers exhibit a tendency to fibrillate when subjected to mechanical stress in the wet state. Fibrillation means that the fiber structure breaks down in the longitudinal direction. Mechanical abrasion in the wet state causes the fine fibrils to partially peel off from the fiber, giving the fabric a hairy appearance. This phenomenon occurs during wet fabric processing steps such as dyeing or scouring, and during washing. The surface of the fabric has an unacceptable appearance. As the fibrils entangle with each other, the surface of the fabric becomes matte, and when fibrillation occurs, the fabric has a lighter color due to the spectral reflection from the surface of the fibrils. Fibrillation usually occurs at the high points of the fabric, and white lines may appear where fibrillation occurs above the creases.

[0006] Fibrillation of the fabric can occur whenever the fabric is subjected to wet abrasion. This can occur during wet processing of the fabric, for example, during jet dyeing or washing of a garment.

[0007] There have been intensive efforts to reduce fibrillation of Lyocell fibers by treating the fibers with crosslinking agents during their manufacture. Suitable processes are described, for example, in EP 0785304, WO 95 / 28516 and WO 99 / 19555. A crosslinking agent is applied to the fibers, preferably fibers that have not been dried at all. This is then subjected to conditions that cause the agent to react with the cellulose in the fibers, causing the cellulose molecules to adhere to each other more strongly than would be possible with the natural hydrogen bonds that normally bind the molecules in the fibers. The hydrogen bonds can be broken by wetting with water, and thus fibrillation can occur. The bonds formed with the crosslinking agent cannot be broken by exposure to water, and therefore the fibers do not fibrillate. Commercially available crosslinked Lyocell fibers are, for example, LENZING® Lyocell A100 and LENZING® Lyocell LF.

[0008] The crosslinked fibers should be able to withstand the mechanical and chemical treatments required to convert the fibers into fabrics, as well as the dyeing and finishing processes that the fabrics are subjected to, without fibrillation, which means that the crosslinked lyocell fibers should be able to be converted into finished fabrics using conventional textile processing and processing machinery.

[0009] It is highly desirable that the treatment to prevent fibrillation renders the fiber at least as dyeable as cotton fiber in the subsequent processing of dyeing, finishing and washing. It should also have the ability to be processed in dyeing and finishing systems that use either acidic or alkaline media. The crosslinking treatment should be stable during storage without the need for special storage conditions.

[0010] Crosslinked lyocell fibers need to be stable in acidic media when blended with other fiber types such as wool, polyester and nylon and then dyed. These fibers require acidic conditions for the dye systems used to color them. The conditions are typically pH 5 at temperatures below 130°C.

[0011] Crosslinked lyocell fibers need to be stable in alkaline media when blended with cotton or other cellulosic fibers. Cellulosic fibers are most commonly dyed using reactive dyes, as they give bright, deep colors with high fastness. Alkaline conditions may range from 40 to 80°C and reach a pH of 12 to 13.

[0012] It is also beneficial that the crosslinking chemistry used does not release formaldehyde during any stage of wet processing.

[0013] However, none of the known anti-fibrillation treatments for Lyocell fibers can provide all of the above listed properties or processing requirements at once.

[0014] EP0538977 and EP0785304 disclose the use of certain chlorotriazine compounds for crosslinking Lyocell fibers. These compounds react with cellulose under alkaline conditions to crosslink the cellulose. These compounds are commercially available and well-known materials. EP0903434 proposes further chlorotriazine compounds to be used as crosslinking agents for Lyocell fibers.

[0015] One exemplary compound used by EP 0538977, sodium-p-[(4,6-dichloro-1,3,5-triazin-2-yl)amino]benzenesulfonate, hereafter referred to as SDTB, is applied to the lyocell fibers in the form of a solution according to EP 0538977. This compound has low solubility in water at room temperature, but is soluble in alkaline media.

[0016] WO 95 / 28516 mentions that the fibrillation protection provided by the polyhalogenated polyazines described in EP 0 538 977, or compounds containing polyazine rings with two or more vinyl sulfone groups, or precursors thereof, tends to be lost when fabrics containing the treated fibers are scoured and washed. The present inventors have also found that using the procedures described in EP 0 538 977 results in fibers with insufficient fibrillation protection against textile processing and washing.

[0017] WO 03 / 038164 mentions that crosslinking agents that are not soluble under alkaline conditions need to be applied to the lyocell fibers in the form of a dispersion, which leads to uneven treatment effects.

[0018] Further state of the art for treating lyocell fibres with crosslinking agents is known, for example, from EP 0691426 A2, WO 2005 / 073443 and WO 94 / 09191.

[0019] There are several methods for the measurement of fibrillation tendency.

[0020] Wet abrasion value (called NSF value) This method determines the ability of a fiber to withstand abrasive forces under wet conditions. The fiber is rotated on a roll and subjected to abrasion. The number of revolutions until the fiber is frayed is determined.

[0021] As a guideline, with regard to the NSF, 50 to 150 revolutions are representative of fibrillating fibers, while fibers exhibiting 200 or more, and especially 400 or more revolutions, will not fibrillate during conventional wetting processes and can be considered as resistant to fibrillation.

[0022] Disintegration test according to TAPPI standard T227om-94 Canadian Standard Freeness (CSF) The susceptibility of a fiber to fibrillation during mechanical work in the wet state can be measured using the CSF test (Canadian Standard Freeness according to TAPPI standard T227om-99).

[0023] This test was originally developed in the paper industry to evaluate the degree to which pulp has been beaten, meaning that it has been broken down into smaller and smaller pieces. In the case of man-made fibres, a dilute aqueous slurry of fibres is subjected to mechanical work under standard conditions and the drainage characteristics of the dilute suspension of fibres are then measured.

[0024] It measures the rate at which a dilute suspension of fibers drains, the so-called freeness at 20° C. As the degree of fibrillation increases, the freeness of the slurry decreases.

[0025] Unfibrillated Lyocell fibers without fibrillation protection show a starting CSF of about 700 (Lenzinger Berichte, 84 (2005) 110-115), but this CSF drops very quickly after just a few minutes of blending. Lyocell fibers with fibrillation protection should show only small changes in freeness value up to 36 minutes after blending (Lenzinger Berichte, 84 (2005) 110-115).

[0026] It has been found that fibers exhibiting high NSF but low CSF do not withstand mechanical stress during wet processing, i.e., are not resistant to fibrillation during wet processing, whereas fibers having both high NSF and CSF are protected from breaking down into fibrils under mechanical stress during wet processing. Summary of the Invention [Problem to be solved by the invention]

[0027] It is an object of the present invention to provide lyocell fibers with stable and permanent fibrillation protection. By "stable" fibrillation protection is meant a low tendency to fibrillate, both in terms of NSF and CSF values. By "permanent" fibrillation protection is meant a fibrillation protection that is not lost during treatment of the fibers under acidic or alkaline conditions, i.e. within the pH range of 5-14. [Means for solving the problem]

[0028] This object is achieved by a method for treating lyocell fibres, comprising the steps of contacting the fibres with at least one treatment medium, the at least one treatment medium containing an amount of a crosslinking agent capable of crosslinking cellulose under alkaline conditions and having a solubility in water at 20°C of less than or equal to 20 g / l, and treating the fibres with the crosslinking agent under alkaline conditions, characterized in that in the step of contacting the fibres, the crosslinking agent is present in the form of a suspension or in solid form.

[0029] Preferred embodiments are set forth in the dependent claims. [Brief description of the drawings]

[0030] [Figure 1] FIG. 2 is a UV-micrograph of lyocell fibers after contact with a crosslinking agent according to the present invention. [Diagram 2] FIG. 2 is a UV-microscope photograph of Lyocell fibers after contact with a crosslinking agent according to the state of the art of EP0538977. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0031] The present invention employs crosslinking agents that crosslink cellulose under alkaline conditions but that are not or only poorly water soluble at room temperature.

[0032] The chemical reaction of the crosslinking agent with the cellulose can take place in two steps: in a first step, the crosslinking agent forms a primary bond with the fiber through one of its functional groups.

[0033] In a second step, the crosslinker, through its further functional groups, forms a second bond with the fibres, whereby the fibres, or the cellulose molecules within the fibres, respectively, are bonded to each other, i.e. they are crosslinked.

[0034] Depending on the nature of the crosslinking agent, the first bond with the fiber can be formed under mild conditions (such as a neutral pH value), whereas the formation of the second bond requires more severe conditions (such as an alkaline pH value).

[0035] The present invention uses a cross-linking agent that requires alkaline conditions to form at least said second bond with the fiber.

[0036] Furthermore, the present invention uses crosslinkers that are not soluble or are very poorly soluble in water at 20° C., ie, have a solubility in water at 20° C. of 20 g / l or less.

[0037] On the other hand, preferably the cross-linking agent used may have a certain low solubility in water at room temperature, such as 5 g / l or more.

[0038] A crosslinking agent that meets these conditions is p-[(4,6-dichloro-1,3,5-triazin-2-yl)amino]benzenesulfonic acid and / or its sodium salt (SDTB). As mentioned above, according to EP 0 538 977, this type of agent is applied to the lyocell fibers in the form of a hot alkaline solution. As also mentioned above, this treatment method has been found not to lead to satisfactory results.

[0039] In contrast, it has surprisingly been shown that the objects of the invention can be achieved by applying the crosslinking agent defined above to the lyocell fibers in the form of a suspension instead of a solution or in solid form.

[0040] For the purposes of the present invention, a suspension means a mixture of crosslinker and a liquid (such as, in particular, water) in which the crosslinker is dissolved to an extent of up to 50%.

[0041] Those skilled in the art know that impregnating a fiber with a suspension of particles results in a non-uniform and punctual distribution of chemical reagents on the fiber surface, which one would expect to result in non-uniform fiber properties.

[0042] Surprisingly, it has been found that for the crosslinking agents defined above, the fibrillation protection of the Lyocell fibers is durable and stable when the crosslinking agent is applied to the fibers in aqueous suspension, i.e. when the treatment medium containing the crosslinking agent is an aqueous suspension of the crosslinking agent.

[0043] A preferred embodiment of the invention is characterized in that the step of contacting the fibers with the treatment medium comprises at least a first contacting step and a second contacting step.

[0044] Preferably, a first process medium is used in the first contacting step and a second process medium is used in the second contacting step, and the composition of the first process medium is different from the composition of the second process medium.

[0045] One of the two treatment media may contain the majority of the total amount of cross-linking agent used. Preferably, the first treatment medium contains the majority of the total amount of cross-linking agent used.

[0046] The concentration of the cross-linking agent in the treatment medium, or in said first treatment medium and / or in the second treatment medium, may be in the range of 5 to 200 g / l, especially in the case of SDTB.

[0047] The respective concentrations of the cross-linking agent in the first and second treatment medium may be different from each other, in particular the concentration of the cross-linking agent in the first treatment medium may be higher than the concentration of the cross-linking agent in the second treatment medium.

[0048] The second treatment medium may contain no cross-linking agent or may contain an insignificant amount of cross-linking agent.

[0049] Preferably, the first treatment medium is an aqueous suspension of the cross-linking agent.

[0050] At least one of the first process medium and the second process medium may be alkaline.

[0051] Preferably, only the second treatment medium is alkaline.

[0052] The temperature of the contacting step may be from 10°C to 50°C.

[0053] The conditions of the step of contacting the fibers with the crosslinking agent, in particular the pH value and / or the temperature of the medium, can be adjusted by the person skilled in the art, and the crosslinking agent should be selected so that it does not dissolve in the treatment solution or dissolves only to a small extent, so that the fibers are impregnated with the crosslinking agent mainly on their surface.

[0054] The step of treating the fibers with a cross-linking agent after contacting the fibers means that the fibers and the cross-linking agent remain in contact for a period of time during which the cross-linking reaction takes place. Depending on the conditions of the contacting step, part of the cross-linking reaction, such as the formation of said first bonds with the cellulose fibers, may already take place during the contacting step.

[0055] In the step of treating the fibers after contacting the fibers with the cross-linking agent, the conditions may be such that the cross-linking agent is soluble or becomes soluble. The conditions should be selected so that the cross-linking agent can form said second bonds with the cellulose fibers.

[0056] In particular, the temperature in the step of treating the fibers with the crosslinking agent may be higher than the temperature in the step of contacting, preferably 60°C to 120°C, more preferably 80°C to 110°C.

[0057] In a preferred embodiment, the step of treating the fibers with a cross-linking agent is carried out in the presence of steam.

[0058] In particular, the step of treating the fibers with a crosslinking agent may be carried out in a steam chamber, such as a J-box.

[0059] Exposing the fibers to high temperature conditions, especially steam, during the crosslinking reaction is known per se.

[0060] It should be mentioned that the steps of contacting the fibre and treating the fibre do not have to be carried out in different reagent vessels, but may be carried out in only one vessel by changing the conditions stepwise.

[0061] The method of the present invention can be applied to fibers both in the chopped form, i.e., in the form of staple fibers, and in the form of infinite filaments, i.e., in the form of a tow.

[0062] Preferably, the fibers are present in the form of a tow.

[0063] Moreover, preferably, the method is performed continuously.

[0064] In a further preferred embodiment, the fiber contacting and treating steps are carried out with the fibers in a never-dried form, the term "never-dried" meaning that the fibers have not yet undergone a drying step since being formed into a fiber by extrusion through a spinneret, as known to those skilled in the art.

[0065] The cross-linking agents used according to the present invention are essentially soluble at pH values ​​of 13 and above.

[0066] Therefore, the step of treating the fibers with a crosslinking agent may preferably be carried out at a pH value of 13 or higher.

[0067] Preferably, the cross-linking agent is p-[(4,6-dichloro-1,3,5-triazin-2-yl)amino]benzenesulfonic acid and / or its salts, in particular the sodium salt thereof (SDTB).

[0068] By using a suspension of SDTB to contact the fibers, it was found that the SDTB particles are located on the surface of the fibers and do not penetrate into the fibers (see Figure 1). During the cross-linking step, for example by heating the impregnated fibers in a steamer, it is believed that the SDTB becomes soluble and thus forms a uniform cross-linked cellulose fiber surface film that protects the fibrils from splitting. It was found that the uniform cross-linked surface results in homogenous fiber properties, such as dye uptake.

[0069] As mentioned above, Lyocell fibers treated by the method of the present invention have been found to exhibit stable fibrillation properties, i.e., both wet abrasion values ​​(NSF) and CSF values.

[0070] The object of the present invention is therefore also achieved by a Lyocell fibre obtainable by the process according to the invention, i.e. crosslinked with a crosslinking agent as defined above, characterized in that it exhibits a wet abrasion value of more than 200 revolutions and a Canadian Standard Freeness value in ml CSF after blending for 9 minutes that is at least 80% of the Canadian Standard Freeness value in ml CSF of the fibre before blending.

[0071] Preferably, the lyocell fibers of the present invention exhibit a wet abrasion value of 400 revolutions or greater.

[0072] The wet abrasion values ​​of the lyocell fibers of the present invention can reach amounts of up to 1000, up to 2000, up to 3000, or even more revolutions.

[0073] Furthermore, the lyocell fibers according to the present invention preferably exhibit a Canadian Standard Freeness value in ml CSF that is at least 80% of the Canadian Standard Freeness value in ml CSF of the fibers prior to blending.

[0074] Furthermore, the fibrillation protection achieved by the Lyocell fibers according to the invention has been found to withstand the conditions of many commonly applied steps of textile article processing, such as dyeing processes, over a wide range of pH values.

[0075] The lyocell fibers according to the invention may be in the fineness range of 0.9 to 3.0 dtex, preferably 1.3 to 1.7 dtex.

[0076] The present invention also encompasses the use of the lyocell fibers according to the present invention for making textile articles such as yarns and fabrics.

[0077] Additionally, the present invention also encompasses textile articles, such as yarns and fabrics, that contain the lyocell fibers according to the present invention. EXAMPLES

[0078] Test Method Wet Abrasion Value (NSF) The method used was that described in the publication by Helfried Stover: "Zur Fasernassscheuerung von Viskosefasern" Faserforschung and Textiltechnik 19 (1968) Issue 10, p. 447-452.

[0079] The device used is the Abrasion Machine Delta 100 from Lenzing Technik Instruments from the publication cited above. In order to prevent the formation of grooves in the filament hose, the steel shaft is moved continuously longitudinally during the measurement.

[0080] Filament hoses supplier: Vom Baur GmbH & KG.Marktstraβe 34,D-42369 Wuppertal

[0081] 20 fibres, 38 mm long, are placed on a metal roll with a thickness of 1 cm and pressed down by a pre-tensing weight. The roll is covered with a stocking of viscose filament yarn and is continuously moistened. During the measurement, the roll is rotated at a speed of 500 revolutions per minute and at the same time rotated back and forth obliquely to the fibre axis, which causes a pendulum movement of approximately 1 cm.

[0082] The number of revolutions until the fiber frays and the preload causes contact is determined.

[0083] Test conditions Water flow rate: 8.2ml / min Rotation speed: 500U / min Wear angle: 40° Pre-applied weight: 50mg

[0084] The average of 20 abrasion cycles of the fibers is taken as the measurement: the more revolutions the fiber has before it wears out, the less fibrillation of the fiber has occurred.

[0085] Canadian Standard Freeness Test (CSF) To test the fibrillation of Lyocell fibers, the fibers were cut into 5 mm lengths and 3.3 g of air-dried fibers were placed in 1000 ml of tap water in a graduated cylinder, the top of the cylinder was closed, and the cylinder was gently inverted 180° three times.

[0086] The fiber suspension is transferred to a Canadian Standard Freeness Tester according to TAPPI T227 om-99 (manufactured by Lorentzen & Wetters, Sweden). The temperature and CSF value are measured. The weight of the sample is determined after drying in an oven at 105°C for 4 hours. The measured CSF results are corrected to take into account the concentration and temperature of the fiber slurry. The correction is based on the following formula:

[0087] Density correction = (X-0.3)×590×(1+(((0.4-X) / 0.2)×(C / 1000)))×(1-((C-390) 2 / ((C 0.2 )×87000))) Temperature correction=(20-T)×4.6×(1-(((400-C) 2 ) / ((C 0.25 )×61000)))

[0088] [In the formula, X = fiber slurry concentration T = temperature of fiber slurry C=measured CSF].

[0089] The two resulting correction values ​​are then respectively added to or subtracted from the CSF measured in any order.

[0090] This represents the CSF value in the wet state for a non-fibrillated fiber sample that has not yet been subjected to mechanical stress. As mentioned above, non-fibrillated Lyocell fibers without fibrillation protection exhibit a starting CSF of about 700 (Lenzinger Berichte, 84 (2005) 110-115).

[0091] To break down the fibres, a blender (Waring blender 8011EB model 38BL41) with a 1 litre stainless steel container with two lids filled with a fibre suspension of 3.3g lutro fibre in 500ml tap water is run at a speed of 18000RPM for a period of time during which fibrillation can occur. The longer the blender is run, the more likely the fibres are to fibrillate. After blending, the fibre slurry is transferred to a graduated cylinder and diluted with tap water to 1000ml of suspension, the cylinder is gently inverted 180° three times, the CSF is measured and the value corrected as above.

[0092] The blender unit / equipment must be calibrated for blend stringency.

[0093] For this purpose, a reference sample of standard lyocell fibre (1.3 dtex / 38 mm cut length, tensile strength conditioned 36 cN / tex, elongation conditioned 13%, light colour, exhibiting a starting CSF of 700 ml), such as LENZING™ lyocell, is used.

[0094] The fibers are blended for 4 and 6 minutes, respectively, and the CSF value is determined. After 4 minutes of blending, the CSF value should be less than 200 ml, and after 6 minutes of blending, the CSF value should be less than 100 ml.

[0095] If these thresholds are not met, the blend strength of the device used is adapted until these values ​​are reached.

[0096] Fiber Preparation Method 1 The aqueous solution of cellulose and NMMO was extruded into an aqueous coagulation bath to form 1.3 dtex filaments of lyocell. After washing with water, all excess NMMO was removed and the lyocell filaments were squeezed to a moisture content of 125% and chopped into 20 cm long fiber bundles.

[0097] Fiber preparation method 2 An aqueous solution of cellulose and NMMO was extruded into an aqueous coagulation bath to form 1.3 dtex filaments of lyocell. The filaments were washed with water to remove any excess NMMO, pressed to a moisture content of 150-200%, and then further processed.

[0098] Example 1 Lyocell filaments were produced by fiber preparation method 2 and then passed through a first impregnation tank, in which 8.3% by weight of SDTB relative to the cellulose was introduced into a water circulator at a temperature of 50° C., giving a concentration of 40 g / l of aqueous pasty suspension. The filaments were pressed to a moisture content of 110-140% and then passed through a second impregnation tank at 10° C., in which 1.34% by weight of NaOH and 1.1% by weight of Na2CO3 relative to the cellulose were introduced into a water circulator. The filaments were then pressed to a moisture content of 160-190%, heated to 100° C. for 9 minutes in a steam chamber, then acid water (pH 3.5) was added, then thoroughly washed with water until free of excess chemicals and dried.

[0099] Example 2 Lyocell filaments were produced by fiber preparation method 2 and then passed through a first impregnation tank, in which 8.3% by weight of SDTB relative to the cellulose was introduced into the water circulation device at a temperature of 35° C., giving a concentration of 40 g / l of aqueous pasty suspension. The filaments were pressed to a moisture content of 180-210% and then passed through a second impregnation tank at 10° C., in which 1.34% by weight of NaOH and 1.1% by weight of Na2CO3 relative to the cellulose were introduced into the water circulation device. The filaments were then pressed to a moisture content of 170-200%, heated to 100° C. in a steam chamber for 8.5 minutes, then acid water (pH 3.5) was added, then thoroughly washed with water until free of excess chemicals and dried.

[0100] Example 3: Reference to EP0538977, Example 4f Lyocell filaments were produced by fiber preparation method 1. A bundle of 30 g of never-dried Lyocell fibers was impregnated for 30 seconds at 70° C. in a 600 g aqueous bath made by combining a hot solution of Thiotan R at 70° C., a solution of Na2CO3 at 70° C. and a solution of Na2SO4 at 70° C. (final concentrations: 50 g / l Thiotan R (= 13 g / l SDTB), 20 g / l Na2CO3, 100 g / l Na2SO4). The fibers were pressed on a foulard at 3 bar and heated to 102° C. in a steam chamber for 20 minutes. The filaments were washed to neutrality with 600 g of an aqueous solution of acetic acid at a concentration of 1 g / l. The fibers were dried overnight at 60° C.

[0101] Reference Example 4 Lyocell filaments were produced by fiber preparation method 2 and then passed directly into an impregnation bath with 9.5% by weight SDTB, 2.7% by weight NaOH and 1.1% by weight Na2CO3 relative to the cellulose at a temperature of 10°C, which was then fed into a water circulation device and passed directly into an impregnation bath with a concentration of 92 g / l SDTB. The SDTB dissolved in the bath to an extent of more than 50%. The filaments were then pressed to a moisture content of 150-170% and heated to 100°C for 8.5 minutes using a steam chamber, then acid water (pH 3.5) was added, and the filaments were then washed with water until no excess chemicals remained and dried.

[0102] Example 5 Lyocell filaments were produced by fiber preparation method 2 and then passed through a first impregnation tank, in which 8.1% by weight of SDTB and 0.35% by weight of NaOH relative to the cellulose were introduced into the water circulation device at a temperature of 50° C., giving a concentration of an aqueous pasty suspension of 58 g / l. The filaments were pressed to a moisture content of 160-190% and then passed through a second impregnation tank at 10° C., in which 1.2% by weight of NaOH and 1.1% by weight of Na2CO3 relative to the cellulose were introduced into the water circulation device. The filaments were then pressed to a moisture content of 160-190% and heated in a steam chamber to 100° C. for 8.5 minutes, then acid water (pH 3.5) was added, then thoroughly washed with water until free of excess chemicals and dried.

[0103] The fibers were analyzed for their Wet Abrasion Value (NSF) and CSF values, and the results are compared in the table below.

[0104] [Table 1]

[0105] Reference Example 3 is an example according to the state of the art known from EP 0 538 977. It can be seen that whilst the wet abrasion values ​​of these fibres appear to be sufficient, the CSF values ​​drop significantly after 9 minutes of blending.

[0106] In Reference Example 4, due to the conditions used in the contacting step, more than 50% of the SDTB was dissolved. Again, a significant decrease in CSF value is observed.

[0107] Examples 1, 2 and 5 are examples according to the invention. All examples show sufficient wet wear values, but in addition, show CSF values ​​that are still very high after blending, i.e., more than 85% of the original value 9 minutes after blending.

[0108] Resistance of fibrillation properties to fabric processing steps The fibers according to the invention were processed into knitted fabrics.

[0109] The knitted fabric was subjected to various wet processing treatments typical of textiles, including both acidic and alkaline environments, the surface of the knitted fabric was found by optical evaluation to remain clean without exhibiting a hairy appearance caused by fibrillation or pilling of tangled fibrils, and the fibrillated properties were found to remain protected, at least to some extent, after being subjected to various conditions, such as reactive (alkaline) dyeing and dyeing under conditions suitable for dyeing polyester (acid dyeing), as determined by wet abrasion values.

[0110] Ring yarn Nm50 / 1 Alpha 105 from fibers according to the invention was used to produce a single jersey fabric having a basis weight of about 130 gsm.

[0111] Prior to dyeing, the fabric samples were washed in a 5 liter beaker at 80° C. for 20 minutes using a Labomat Type BFA-12 from Mathis, Switzerland, with a liquor ratio of 1:30 and a rotation of 20 rpm.

[0112] The following wash solution was prepared: 1 g / l of a textile finishing detergent, e.g. Kieralon JET, a trademark of BASF, 1 g / l of sodium carbonate, 1 g / l of a wetting agent, e.g. Albaflow FFA, from Huntsman, and 1 g / l of a lubricant, e.g. Persoftal L, from Tanatex Chemicals. After washing, the fabrics were rinsed hot and cold.

[0113] The dyeing of the fabric was also carried out in a Labomat Type BFA-12 in a 5 liter beaker with a liquor ratio of 1:30 and a rotation speed of 20 rpm.

[0114] Example 1 Heat-reactive dyeing (alkaline) Composition of dyebath using soft water: 4.0% Huntsman brand Novacron marineblau FG 40g / l sodium sulfate (salt) 6g / l sodium carbonate 1g / l lubricant 1g / l defoamer

[0115] The fabric and the dyebath were heated to 60°C in a labomat with a heating rate of 6°C per minute. When the dyebath reached 60°C, the dye, lubricant and defoamer were added. After 25 minutes, the salt was added, and after 5 minutes, the sodium carbonate. After 15 minutes, at 60°C, the bath was drained and the fabric was rinsed in water at 20°C for 10 minutes and then drained. The fabric was then treated with 1 ml / l acetic acid (60%) at 40°C for 10 minutes. The water was then drained and the fabric was then rinsed in water at 40°C for 10 minutes. The bath was drained and then soaping was performed, which means that the fabric was treated with a washing liquor (Kieralon JET 1 g / l in soft water) at 90°C. The bath was drained and the fabric was rinsed one last time with tap water at 20°C for 10 minutes and then drained. The fabric was then hung on a needle frame and dried at room temperature.

[0116] After this procedure, the surface of the blue fabric remained completely clean without showing any fibrillation. The fibers removed from the dyed fabric did not show any decrease in NSF value compared to the NSF value of the original fibers before dyeing.

[0117] The wash performance of the dyed fabric was tested by performing 10 domestic washes using mild detergent at 40°C in a domestic washing machine. After each wash step, the fabric was dried in a tumble dryer. After this procedure, visual inspection showed that the surface of the fabric was still good, no pilling or greying was observed, only small negligible fiber splices were observed.

[0118] Example 2 Hot Acid Dyeing ("Polyester Dyeing") Composition of dyebath using soft water: 1.0% DyStar trademark Dianix blue FBL 1g / l sodium acetate 1g / l lubricant 1g / l anionic anti-wrinkle agent Adjust the pH of the dyebath to 4.5 with acetic acid.

[0119] The dyebath with the fabric was heated to 130° C. at a heating rate of 2° C. per minute and held at 130° C. for 60 minutes. After cooling to 70° C. at 2° C. per minute, hot and cold rinses were performed followed by reductive cleaning.

[0120] Composition of reduction cleaning bath: 2g / l sodium hydrosulfite 2ml / l of 34% caustic soda solution 1g / l lubricant

[0121] The fabric and cleaning bath with a liquor ratio of 1:30 were heated at 6°C / min to 80°C in a lab mat at 20 rpm. After 20 minutes at 80°C the bath was drained and the fabric was rinsed in water at 20°C for 10 minutes and then drained. The fabric was then treated with 1 ml / l acetic acid (60%) at 40°C for 10 minutes. The water was then drained and the fabric was then rinsed in water at 40°C for 10 minutes. The bath was drained and the fabric was finally rinsed in water at 20°C for 10 minutes and then drained. The fabric was then hung on a needle frame and dried at room temperature.

[0122] After this procedure, the surface of the light blue fabric remained completely clean and showed no fibrillation. The fibers removed from the dyed fabric showed no decrease in NSF value compared to the NSF value of the original fibers before dyeing.

[0123] The wash performance of the dyed fabric was tested by performing 10 domestic washes in a domestic washing machine at 40°C using a neutral detergent. After each wash step, the fabric was dried in a tumble dryer. After this procedure, by visual inspection, the surface of the fabric was not different from the dyed fabric before washing. The acidic dyeing conditions do not have a negative effect on the wash performance of the fabric.

Claims

1. A method for treating lyocell fibers, comprising the steps of contacting the fibers with at least one treatment medium, the at least one treatment medium containing an amount of a crosslinking agent capable of crosslinking cellulose under alkaline conditions and having a solubility in water at 20°C of less than or equal to 20 g / l, and treating the fibers with the crosslinking agent under alkaline conditions, characterized in that in the step of contacting the fibers, the crosslinking agent is present in the form of a suspension or in solid form.

2. The method of claim 1 , wherein the step of contacting the fibers with a treatment medium comprises at least a first contacting step and a second contacting step.

3. 3. The method of claim 2, wherein the first contacting step uses a first treatment medium and the second contacting step uses a second treatment medium, the first treatment medium and the second treatment medium having different compositions.

4. 4. The method according to claim 2 or 3, characterized in that the first treatment medium contains the majority of the total amount of crosslinking agent used.

5. 5. The method according to claim 3 or 4, characterized in that the first treatment medium is an aqueous suspension of the crosslinking agent.

6. 6. The method according to claim 3, wherein at least one of the first and second treatment media is alkaline.

7. 7. The method of claim 6, wherein only the second treatment medium is alkaline.

8. The method according to any one of claims 1 to 7, characterized in that the temperature of the contacting step is from 10°C to 50°C.

9. 9. The method according to claim 1, wherein the temperature of the step of treating the fibers with the crosslinking agent is higher than the temperature of the step of contacting.

10. The method according to claim 9, characterized in that the temperature of the step of treating the fibers with a crosslinking agent is between 60°C and 120°C.

11. The method according to claim 9, characterized in that the temperature of the step of treating the fibers with a crosslinking agent is between 80°C and 110°C.

12. 12. The method according to any one of claims 1 to 11, characterized in that the step of treating the fibres with a crosslinking agent is carried out in the presence of steam.

13. 13. The method of claim 12, wherein the step of treating the fibers with a cross-linking agent is carried out in a steam chamber.

14. 14. The method according to any one of claims 1 to 13, characterized in that the fibers are present in the form of a tow.

15. 15. The method according to any one of claims 1 to 14, characterized in that it is carried out continuously.

16. 16. The method according to any one of claims 1 to 15, characterized in that the steps of contacting and treating the fibres are carried out with the fibres in a completely undried form.

17. 17. The method according to any one of claims 1 to 16, characterized in that the crosslinker is essentially soluble at a pH value of 13 or higher.

18. 18. The method according to any one of claims 1 to 17, characterized in that the crosslinking agent is p-[(4,6-dichloro-1,3,5-triazin-2-yl)amino]benzenesulfonic acid and / or its salts.

Citation Information

Patent Citations

  • Method of treating solvent spinning cellulose fiber

    JP1993117970A

  • Fiber processing

    JP1997512062A

  • Treatment of cellulose fiber

    JP2000064176A

  • Method for treating cellulose molded body

    JP2001505970A

  • Processing process of solvent-spun cellulose fibers

    JP2005507035A